Solutions manual for statistics for management and economics a systematic approach - Keller, Gerald; Warrack, Brian (Duxbury Press, 1994)
STATISTICS FOR MANAGEMENT AND ECONOMICS is the worldwide best selling business statistics text. It is currently being used at hundreds of colleges and universities throughout the world. This text teaches students how to apply statistics to real business problems through the authors' unique three-step approach to problem solving. Students learn to IDENTIFY the right technique by focusing on the relationship between the problem and data type. They then learn to COMPUTE the answer either by hand, using Excel, or using MINITAB. Finally, they INTERPRET the results in the context of the problem. This approach enhances student comprehension as well as practical skills, and offers maximum flexibility to instructors wishing to teach concepts by hand or with the computer, or by using both hand and computer methods.